Relevance of arts and social sciences subjects to security and safety education upper basic schools - Owoyale-Abdulganiy , Ibrahim Solahudeen; Olokooba, Nasiru; Ayuba , Olaniyi Jibril (Universitas Majalengka, 2023)
This paper investigated the relevance of Arts and Social Sciences Education in the promotion of security and safety education in Nigeria. This paper examined religious, social and language roles in ensuring security and safety of lives and properties in the country. The objectives of the study were to examine relevance of religious, language and Social Studies to security and safety education as the country persistently experienced security challenges. The simple random sampling technique was used to select 50 out of 120 teachers of Religious Studies, 55 out of 135 teachers of language education and 53 out of 315 teachers of social studies in upper basic schools in Ilorin, Kwara State, Nigeria. A researchers-designed questionnaire titled “Relevance of Arts and Social Sciences to Security and Safety Education Questionnaire (RASSSSEQ)” was used to gather data from the respondents. The instrument was validated by three experts in Test and Measurement and found it appropriate for this study. The reliability of the instrument was determined using test re-test reliability technique within a two-week interval. The scores of the two tests were correlated using the Pearson’s Product Moment Correlation (PPMC). The value obtained was 0.87. Three research questions raised were answered using the percentages. The findings of the study revealed that Arts and Social Sciences subjects are relevant in ensuring security and safety education in our society. The study concluded that curriculum must be reviewed in other to promote security education through Arts and Social Sciences subjects. Also, the study recommended that ministry of education should include security and safety education in social studies, languages and religious studies curriculum at all levels of education.